PENGARUH PEMBERIAN KOMBINASI ANTI RETRO VIRUS LEBIH AWAL TERHADAP MORTALITAS PADA KO-INFEKSI TB-HIV DI RUMAH SAKIT SANGLAH DENPASAR - Utama, Susila (journal of internal medicine, 2011)
TB and HIV are closely interlinked. TB is a leading cause of HIV-related morbidity and mortality. Mortality amongpatients with TB-HIV co-infection is known to be high despite the use of effective TB treatment. Many studies have indicatedthat the initiation of Combination Anti Retro Virus (cARV) during TB treatment improves outcomes. The optimal timing forthe initiation of cARV in patients with TB-HIV co-infections remains unclear. The aims of this study is to know the impact ofearly initiation of cARV during TB treatment on mortality in TB-HIV co-infected patients at Sanglah Hospital Denpasar. Cohortretrospective study was conducted from medical record of TB-HIV co-infected patients from June 2004 until August 2009. Theinclusion criteria was TB-HIV co-infected patients with TB treatment earlier than cARV. The cARV treatment was differentiatedinto 2 category, before 2 months of TB treatment (during intensive phase) and after 2 months (maintenance phase). All of thepatients were followed for mortality after one year of cARV treatment. There were 60 TB-HIV co-infected patients, 50 (83.3%)male and 10 female (16.7%). The CD 4 level less than 50 cell/mm3 were 48 (80%) and CD 4 level more than 50 cell/mm3 were 12(20%). The cARV treatment during intensive phase of TB treatment were 20 (33.3%) and cARV treatment after intensive phasewere 40 (66.7%). Mortality after one year cARV treatment were 28.3%. The mortality on cARV treatment after 2 intensive phasewas 32.5% (13 patients) and mortality on ARV treatment during intensive phase was only 20% (4 patients). The odds ratio was1,926 with confidence interval 0.536 ? 6.926. The mortality on the group of CD 4 level less than 50 cell/mm3 was not different.The mortality on ARV treatment after intensive phase were 34.5% and only 21.1% when cARV during intensive phase. Oddsratio was 1.974 with confidence interval 0.515 ? 7.558. The initiation of cARV during intensive phase of TB treatment on TBHIVco-infected patients will decreased mortality in one year of cARV treatment, but statistically not significance. The sameresult was also found in CD 4 less than 50 cell/mm3.